2021
DOI: 10.1016/j.heliyon.2021.e07247
|View full text |Cite
|
Sign up to set email alerts
|

A collection of the novel coronavirus (COVID-19) detection assays, issues, and challenges

Abstract: The global pandemic of COVID-19 has rapidly increased the number of infected cases as well as asymptomatic individuals in many, if not all the societies around the world. This issue increases the demand for accurate and rapid detection of SARS-CoV-2. While accurate and rapid detection is critical for diagnosing SARS-CoV-2, the appropriate course of treatment must be chosen to help patients and prevent its further spread. Testing platform accuracy with high sensitivity and specificity for SARS-CoV-2 is equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…In COVID-19, infection by SARS-CoV-2 induces the production of IL-6, causing a cytokine storm associated with systemic inflammation 17,18 . Investigations for SARS-CoV-2 infection include genetic tests, such as reverse transcription-polymerase chain reaction (RT-PCR) , and immunological assays targeting the antigen or antibody 19,20 . The RT-PCR test detects SARS-CoV-2 in nasopharyngeal swabs and saliva and is widely used to diagnose COVID-19 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In COVID-19, infection by SARS-CoV-2 induces the production of IL-6, causing a cytokine storm associated with systemic inflammation 17,18 . Investigations for SARS-CoV-2 infection include genetic tests, such as reverse transcription-polymerase chain reaction (RT-PCR) , and immunological assays targeting the antigen or antibody 19,20 . The RT-PCR test detects SARS-CoV-2 in nasopharyngeal swabs and saliva and is widely used to diagnose COVID-19 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Investigations for SARS-CoV-2 infection include genetic tests, such as reverse transcription-polymerase chain reaction (RT-PCR) , and immunological assays targeting the antigen or antibody 19,20 . The RT-PCR test detects SARS-CoV-2 in nasopharyngeal swabs and saliva and is widely used to diagnose COVID-19 20,21 . The immunological antigen test can detect SARS-CoV-2 antigens in nasopharyngeal swabs and diagnose COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several detection methods available, but due to the worldwide need their availability was limited, especially in the first year of the pandemic. Most of these constraints were linked to the lack of equipment and reagents, defective test kits, and excessive waiting time before results, hence the emergency in developing fast, sensitive, and cost-effective tools [1]. Since it has been proven that early detection has a great impact in decreasing the number of cases, it is imperative to enhance the availability and specificity of tests, as well as diminish the time from sample collection to test result [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that micro-sized AuNPs produce reds from light to dark that are visible to the naked eye when they react with the aggregation of gold nanoparticles. This color reaction is related to the size and shape of gold nanoparticles [ 15 , 16 ]. Therefore, if the rapid test strips used for the LFIA react with a particular disease or symptom, their test lines turn magenta, whose concentration indicates the mild, moderate, or severe level of the condition examined [ 4 , 17 ].…”
Section: Introductionmentioning
confidence: 99%